Monoglycerides, polyglycerol esters, lecithin, and their mixtures influence the onset of non‐isothermal fat crystallization in a concentration dependent manner. Issue 11 (14th July 2015) - Daels, Eva; Rigolle, Annelien; Raes, Katleen; De Block, Jan; Foubert, Imogen
Abstract : The objective of this study was to investigate the influence of commercially available monoacylglycerol (M), polyglycerol esters (P), and sunflower lecithin (L) on the onset of crystallization of bulk fat as a function of the added concentration. Not only a single type of emulsifier, but also binary and ternary mixtures of M, P, and L were added to the two different "host" fats using a statistically sound mixture design. The obtained mixtures were analyzed for their non‐isothermal crystallization behavior by differential scanning calorimetry. If a single type of emulsifier was added, the nucleation was accelerated when adding M or P, while L addition had no significant effect. Furthermore, it was shown that the minimum concentration necessary to provoke a nucleation accelerating effect is lower for P than for M. Antagonistic effects between M and L (and not between P and L) were suggested by the coefficient estimates of the special cubic model. Practical applications: Palm oil (PO) is one of the most consumed vegetable oils in the world because of its unique physical properties. It imparts a very high stability to the β′ crystal form, yielding relatively small crystals which give a smooth texture to e.g., margarines and shortenings. Because PO is semi‐solid at room temperature, it forms an ideal hard stock to be used in trans free food products. However, PO has a slow crystallization rate and an unusually long α‐lifetime. These disadvantages can be overcome by the addition of an emulsifier acting as crystallization modifier (e.g., monoacylglycerols and diacylglycerols)1 . Furthermore, from a nutritional point of view, the saturated fatty acids present in PO2, are among the factors contributing to cardio‐vascular diseases3 . When using more unsaturated fats as hard stock, the use of additives in order to avoid compromising the functionality of the food product should be further investigated. This study investigated the influence of commercially available monoacylglycerol (M), polyglycerol esters (P), and sunflower lecithin (L) on the onset of crystallization of bulk fat as a function of the added concentration. Not only a single type of emulsifier, but also binary and ternary mixtures of M, P, and L were added to the two different "host" fats using a statistically sound mixture design. The total amount of emulsifiers in each blend was set to 1.5%. The obtained mixtures were analyzed for their non‐isothermal crystallization behavior by differential scanning calorimetry. It was shown that the effect on the onset of crystallization of the bulk fat depends on the type and the concentration of emulsifier. Abstract : This study investigated the influence of commercially available monoacylglycerol (M), polyglycerol esters (P), and sunflower lecithin (L) on the onset of crystallization of bulk fat as a function of the added concentration. Not only a single type of emulsifier, but also binary and ternary mixtures of M, P, and L were added to the two different "host" fats using a statistically sound mixture design. The total amount of emulsifiers in each blend was set to 1.5%. The obtained mixtures were analyzed for their non‐isothermal crystallization behavior by differential scanning calorimetry. It was shown that the effect on the onset of crystallization of the bulk fat depends on the type and the concentration of emulsifier.